On obligatorily fronted adverbials in German – the case of klar ‘of course’ - Bjarne Ørsnes (Globe, 2023)
In German, almost any kind of constituent can occupy the first position, the prefield, of a declarative clause. Either a constituent is moved there from a base position within the clause or it is filled by a semantically void pronoun. Nevertheless, some expressions such as expressive adverbials rarely occur in the prefield. Meinunger (2022) refers to such expressions as ‘prefield-phobic’. But the opposite is also the case: some expressions only occur in the prefield and not in other positions of the clause or with a different interpretation. An example of such a ‘prefield-philic’ expression is the evidential sentence adverb klar, lit. ‘clear’. In the prefield it means ‘of course’ (Klar weiß ich das! ‘Of course I know’), while it means ‘clearly’ in other positions of the clause (Er hat es ganz klar gewusst. ‘He has clearly known’). The article describes these uses and suggests that there are two sentence adverbs of klar with different histories. One means ‘clearly’ and has developed from the manner adverbial klar by extension of the scope. The other means ‘of course’ and has developed through reanalysis of the adjective klar used as an independent exclamatory utterance (Klar! ‘of course’) into a sentence adverb. The analysis is supported by diachronic evidence and appears to carry over to other prefield-philic expressions.